Philosophy of Education and Technology to Achieve a Balance between Tradition and Innovation - Maisaroh, Ima; Hidayat, Soleh; Sujanah, Nanah; Supiyati; Mehmed, Muhammad Umar (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2025)
The philosophy of education provides a theoretical foundation for integrating traditional moral, ethical, and cultural values with the demands of innovation in the digital age. Educational technologies, such as online learning and artificial intelligence, offer excellent opportunities to expand access to learning and improve efficiency. However, reliance on technology may reduce education's personal and emotional aspects. This research aims to discuss the role of educational philosophy in bridging the balance between tradition and innovation in the era of rapidly developing technology. The method used is descriptive qualitative research with a literature study approach. The study results show that educational philosophy plays a vital role in maintaining the relevance of traditional education through the wise utilization of technology. One example of the application of this concept is blended learning, which allows technology to complement learning without eliminating direct interaction between teachers and students. In addition, educational philosophy emphasizes the importance of character development, social responsibility, and morality of students as essential aspects of education. This research concludes that the integration of tradition and technology must be balanced so that innovation does not come at the expense of the fundamental values of education. With educational philosophy as a guide, technology can enrich the learning process holistically while maintaining a balance between technological efficiency and humanist values.